2020
DOI: 10.3389/fimmu.2020.00593
|View full text |Cite
|
Sign up to set email alerts
|

Myricetin Possesses Anthelmintic Activity and Attenuates Hepatic Fibrosis via Modulating TGFβ1 and Akt Signaling and Shifting Th1/Th2 Balance in Schistosoma japonicum-Infected Mice

Abstract: the first direct evidence that myricin possesses potent anti-schistosome activities in vitro and in vivo, and offers new insights into the mechanisms of action by myricetin. The present findings suggest that myricetin could be further explored as a therapeutic agent for S. japonicum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 52 publications
4
25
0
1
Order By: Relevance
“…Shifts in the Th1 response to the Th2 response are a determining factor in the mechanism of granuloma formation and hepatic fibrosis ( Bourke et al, 2013 ; Qiu et al, 2017 ; Romano et al, 2016 ). Targeting the Th1/Th2 balance in S. japonicum –infected mice can attenuate hepatic fibrosis ( Huang et al, 2020 ). Furthermore, a schistosome infection can also cause a wide range of clinical symptoms such as gut inflammation and affect the gut microbiota of mice ( Hu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Shifts in the Th1 response to the Th2 response are a determining factor in the mechanism of granuloma formation and hepatic fibrosis ( Bourke et al, 2013 ; Qiu et al, 2017 ; Romano et al, 2016 ). Targeting the Th1/Th2 balance in S. japonicum –infected mice can attenuate hepatic fibrosis ( Huang et al, 2020 ). Furthermore, a schistosome infection can also cause a wide range of clinical symptoms such as gut inflammation and affect the gut microbiota of mice ( Hu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The tendency between neutrophils and Th17 cells was consistent in the mice with Schistosomiasis [19] [20]. Yang Q et al identi ed that MDSCs in the spleen of C57BL/6 mice with 5-6wks of 40 ± 5 Sj cercariae infection were strikingly increased [4].Huang P et al [21] showed that Th2, Th17 and CD25 + Foxp3 + CD4 + T cells (Treg) but not Th1 signi cantly increased in the BALB/c mice spleen post 7wks of 30 ± 2 Sj cercariae infection. Tebeje BM et al [22]identi ed that 5wks of 34 Sj cercariae-infected splenic Th1 cells responded more highly to Sj adult worm antigen preparation (SWAP)compared to SEA.…”
Section: Discussionmentioning
confidence: 86%
“…Macrophages are classically divided into M1 and M2 macrophages, and different cell clusters have been detected for marker genes of M1 ( TNF , IL1B , IL12B ) and M2 ( ARG1 , TGFB1 , IL10 ). 3 , 21 TNF was expressed in MP(0), MP(4), MP(5) and MP(7). IL1B was expressed in all clusters except MP(2), MP(3) and MP(8).…”
Section: Resultsmentioning
confidence: 99%
“…1 One type of liver fibrosis, known as schistosomaassociated liver fibrosis, is induced by granulomatous inflammation around eggs deposited in the liver. 2,3 Schistosoma japonicum, S. mansoni and S. mekongi are the main species that will lead to schistosoma-associated liver fibrosis. 4 Importantly, extensive liver fibrosis results in portal hypertension, a leading cause of death in patients with schistosomiasis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation